DAMPAK EKONOMI DIGITAL TERHADAP KETENAGAKERJAAN DI INDONESIAPERIODE 2010-2023 - Irawan, Salsabila; Mulyani, Sherly; Darmawan, Sherly Putri; Paronama, Maya (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
The digital economic transformation in Indonesia has brought significant changes in the dynamics of the labor market. Technological developments, such as automation, artificial intelligence, and digital platforms, create new opportunities as well as challenges for the workforce. On the one hand, the digital economy opens up new jobs in the information technology, e-commerce, and platform-based services sectors. On the other hand, this shift also has the potential to reduce the demand for labor in traditional sectors that have not been digitized. This study analyzes the impact of the digital economy on employment in Indonesia by highlighting changes in skill needs, new job opportunities, and the risk of digital inequality. The results of the study show that adaptation to digital technology and improving the quality of human resources are the main keys to utilizing the potential of the digital economy. Therefore, collaboration between the government, industry players, and educational institutions is needed in developing training programs and policies that support the transformation of a competitive workforce in the digital era.